(untitled) (Medico Legal Update, 2020)
Background: Placenta is a temporary endocrine organ formed during pregnancy, which produces hormones important in the maintenance of a healthy pregnancy. hCG is the first one of these hormone that is measured in pregnancy test and used in the follow up of adverse pregnancy outcome, Alpha fetoprotein is a major plasma protein produced by the yolk sac and the fetal liver during fetal development.Aim of study :to study relationship between gestational complications and levels of maternal serum HCG and AFP and determine whether the semarkers are effective predictors adverse pregnancy outcomes. Patients & Methods:Prospective cohorts study in AlDiwaniyah maternity and pediatrics teaching hospital.We enrolled a total of 230 women at 14-23 gestational weeks and measurement of maternal serum HCG & AFP were done, of those with normal HCG & AFP formed (group l), group 2 involved women with elevated AFP , group 3 with elevated HCG & group 4 involved women with elevated both HCG & AFP.Follow up weekly of the patients for the development of adversepregnancy outcome.Results: A significant relationship between adverse pregnancy outcomes and abnormal elevation of HCG & AFP levels in the second trimester. In group 2 the patients developed higher rate of preterm labour & pre-eclampsia compared with the group 1. In group 3 with raised HCG the rate of pre-eclampsia & IUGR development were higher than group 1. In group 4 with elevated both HCG & AFP higher incidence of pre-eclampsia & placental abruption , with a specificity(p<0.001). Conclusion: In the second trimester unexplained high AFP and HCG rates related to adverse maternal and perinatal outcomes.